Estratigrafía del precretácico en el flanco occidental de la serranía de perijá (1970)
A great number of outcrops of Paleozoic rocks are found in the Cordillera Oriental, however, a continuos stratigraphic section has still not been observed. The principal object of this study is to make such a section in the Serranía de Perijá. The oldest stratigraphic sequence is a series of Cambrian-Ordovician metamorphic rocks which are found near Manaure on the western side of the Serranía de Perijá. This series corresponds to the Quetame Group.  Silurian beds, were not found here, nor have they been reported alsewhere in Colombia. These Cambrian-Ordovician phyllites are covered by fossiliferous Devonian rocks which rest on an erosion surface. The fauna are the Lower and Middle Devonian and permit the correlation of these units with the Caño Grande Formation of the Cachirí Group on the east side of the Serranía de Perijá. Although the presence of the Upper Devonian is possible here, those beds that might correspond to the Caño del Oeste and Campo Chico Formations are lacking. Discordantly covering the Devonian rocks is a series of Pennsylvanian marine sandstones and fossiliferous limestones. The series continues with sandstones, limestones and siliceous limestones. The limestones contain fauna of the Lower and Middle Permian and can be correlated with the Palmarito Formation of the Andes de Mérida. The Triassic- Jurassic is represented by continental units with intercalations of volcanic material that are correlated with the La Quinta Formation Venezuela. These red beds represent the Neogirón Formation of Bürgl (1964). Marine sediments were only newly deposited in the Northern Andes, beginning with the Hauterivian transgression. The Caledonian orogeny folded and uplifted the pre-Devonian series. Since the Sierra Nevada de Santa Marta, Devonian (?) sandstones are found that have black fossilerous limestones in the upper part. Based on fossil evidence, these limestones are dated as from the Pennsylvanian. Stratigraphically, this series is found between the Pre-Cambrian basement gneisses and the Mesozoic volcanic rocks. The Caledonian orogeny folded and uplifted the pre-Devonian series. Since the beginning of the Devonian there is no indication of any metamorphic activity. The tectonics are limited essentially to vertical movements.